LIN YÜ-SHENG, The crisis of chinese consciousness, radical antitraditionalism in the May Fourth Era Madison-Wisconsin, The University of Wisconsin Press, 1979, 201 pp. - -, - (Estudios de Asia y África, 1980)
-